Integrative genomic analysis identifies novel causal genes of Hodgkin’s and non-Hodgkin’s lymphoma - Patrick Shi; Ancha Baranova; Hongbao Cao (Discover Oncology)
Abstract Background The genetic mechanisms underlying non-Hodgkin lymphoma (NHL) and Hodgkin lymphoma (HL) remain understudied. While numerous genes associated with these lymphoid tumors have been identified, little research has focused on the genetic networks that directly drive NHL and HL pathogenesis. Methods We conducted integrative genomic analyses, including a transcriptome-wide association study (TWAS), a proteome-wide association study (PWAS), and a summary-data-based Mendelian randomization (SMR), to identify causal genes for NHL and HL. TWAS and PWAS were performed using FUSION software by integrating GWAS data with gene and protein expression weights from large-scale datasets. The SMR analysis utilized cis-eQTL data to assess causal relationships between gene expression and lymphoma risk. Associations were deemed significant at p < 0.05. Results The PWAS identified 106 proteins associated with NHL and 67 proteins associated with HL. The TWAS revealed 172 genes linked to NHL risk and 448 genes linked to HL risk. Finally, the SMR analysis highlighted 270 genes associated with NHL risk; there was with no evidence of heterogeneity in the HEIDI test, which supports pleiotropic effects. Key genes that influence NHL risk include KRT1, ERAP2, RMDN1, FAS, and C5, while UNC5B was identified as a significant causal gene for HL. Locus and effect plots were used to validate these findings by highlighting causal variants associated with lymphoma risks. Conclusion In this study, KRT1, ERAP2, RMDN1, FAS, C5, and UNC5B were identified as potential causal factors in lymphoma risk, underscoring mechanisms such as immune modulation and tumor suppression and providing insights into future therapeutic targets.